Clinical and virologic follow-up in perinatally HIV-1-infected children and adolescents in Madrid with triple-class antiretroviral drug-resistant viruses. (June 2015) - Rojas Sánchez, P.; de Mulder, M.; Fernandez-Cooke, E.; Prieto, L.; Rojo, P.; Jiménez de Ory, S.; José Mellado, M.; Navarro, M.; Tomas Ramos, J.; Holguín, Á.; ,
Abstract: Drug resistance mutations compromise the success of antiretroviral treatment in human immunodeficiency virus type 1 (HIV-1)-infected children. We report the virologic and clinical follow-up of the Madrid cohort of perinatally HIV-infected children and adolescents after the selection of triple-class drug-resistant mutations (TC-DRM). We identified patients from the cohort carrying HIV-1 variants with TC-DRM to nucleoside reverse transcriptase inhibitors, nonnucleoside reverse transcriptase inhibitors and protease inhibitors according to IAS-USA-2013. We recovered pol sequences or resistance profiles from 2000 to 2011 and clinical–immunologic–virologic data from the moment of TC-DRM detection until December 2013. Viruses harbouring TC-DRM were observed in 48 (9%) of the 534 children and adolescents from 2000 to 2011, rising to 24.4% among those 197 with resistance data. Among them, 95.8% were diagnosed before 2003, 91.7% were Spaniards, 89.6% carried HIV-1-subtype B and 75% received mono/dual therapy as first regimen. The most common TC-DRM present in ≥50% of them were D67NME, T215FVY, M41L and K103N (retrotranscriptase) and L90M (protease). The susceptibility to darunavir, tipranavir, etravirine and rilpivirine was 67.7%, 43.7%, 33.3% and 33.3%, respectively, and all reported high resistance to didanosine, abacavir and nelfinavir. Despite the presence of HIV-1 resistance mutations to the three main antiretroviral families in our paediatric cohort, some drugs maintained their susceptibility, mainly the new protease inhibitors (tipranavir and darunavir) and nonnucleoside reverse transcriptase inhibitors (etravirine and rilpivirine). These data will help to improve the clinical management of HIV-infected children with triple resistance in Spain.